A Comparative Study on GC Analysis of Kernel Fatty Acids of Turkish Walnut (Juglans regia L.) Genotypes - MURADOGLU, FERHAD; BALTA, FIKRI (Asian Journal of Chemistry, 2010)
This work deals with determining kernel fatty acid composition (FAC) on the basis of kernel ground colour in walnut (Juglans regia L.) selections from eastern Turkey. Fruits of 50 promising walnut genotypes were analyzed with respect to their oil and fatty acid composition. Selections with light coloured kernels (LCK) and medium coloured kernels (MCK) were arranged in a row based on their kernel ground colours according to UPOV descriptors (1999). Light coloured kernels and medium coloured kernels selections had mean values of 58.97- 58.04 % for kernel oil, 56.79-57.26 % for linoleic acid, 22.56-21.90 % for oleic acid, 12.28-12.46 % for linolenic acid, 4.35-4.34 % for palmitic acid and 2.03-2.05 % for stearic acid. With respect to unsaturated fatty acids and saturated fatty acids, significant differences were not found between light coloured kernels and medium coloured kernels selections.